A gestao da informaçao e a competência em informaçao: subsídios para o âmbito empresarial - Pinheiro dos Santos, Beatriz Rosa (2017)
Every day, a large volume of information is downloaded onto organizations without a management plan for this resource, damaging the work processes, which require the employee to have effective competence against the use of this information. Thus, this research aims to interrelate the information management and information literacy as processes that can subsidize the work practices of the organizations inserted in the business context. The research problem is defined: how can information management and information literacy contribute to organizations within the business context? Why does information management require Information Competence and vice versa? For this, a research of the bibliographic type and qualitative nature was used as methodology, where a survey of relevant materials on the concepts in question was carried out. The results showed that it is relevant to unite these fields of information science (information management and information literacy) and insert them into the organizational environment, in order to optimize the daily processes related to work practices and decision making. This interrelationship can be identified as strategic planning for the achievement of competitive advantage and success in the market